Pembinaan Pengelolaan Keuangan PEMBINAAN PENGELOLAAN KEUANGAN DAN TEKNOLOGI INFORMASI PADA INDUSTRI SNACK DAN COOKIES BATAM: PENGELOLAAN KEUANGAN DAN TEKNOLOGI INFORMASI - Dian Efriyenty (Jurnal Pengabdian Barelang, 2019)
The problems currently faced are financial reports compiled in each period not yet accounting standard, lack of knowledge and understanding of Micro, Small and Medium Enterprises in the preparation of financial reports to produce financial and information technology information, increased production produced by MSMEs and often neglect not recording financial problems related to material expenditure, production process to marketing, so that prices are formed based on estimates only. In fact, most of the chips and processed cake pasters still don't hold financial records properly. The method used in fostering the Snack And Cookies Industry in Batam City will be given, namely the survey method, lecture method, discussion method and training method. The results of the UKM service felt that there was still a need to adjust to the preparation of financial statements with the financial accounting standards of entities without public accountability, to practice daily input of financial data with Ms. Excel in improving the financial performance of SMEs running smoothly.